2014
DOI: 10.1609/aaai.v28i1.8937
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Helpful Reviews Using Emotions Extraction

Abstract: Reviews keep playing an increasingly important role in the decision process of buying products and booking hotels. However, the large amount of available information can be confusing to users. A more succinct interface, gathering only the most helpful reviews, can reduce information processing time and save effort. To create such an interface in real time, we need reliable prediction algorithms to classify and predict new reviews which have not been voted but are potentially helpful. So far such helpfulness pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…and deep learning based methods (Chen et al, 2019;Fan et al, 2018;Chen et al, 2018). The machine learning based methods employ domain-specific knowledge to extract a variety of hand-crafted features, such as structure features (Kim et al, 2006), lexical features (Krishnamoorthy, 2015), emotional features (Martin and Pu, 2014), and argument features (Liu et al, 2017), from the textural reviews, which are then fed into conventional classifiers such as SVM (Kim et al, 2006) for helpfulness prediction. These methods rely heavily on feature engineering, which is time-consuming and labor intensive.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…and deep learning based methods (Chen et al, 2019;Fan et al, 2018;Chen et al, 2018). The machine learning based methods employ domain-specific knowledge to extract a variety of hand-crafted features, such as structure features (Kim et al, 2006), lexical features (Krishnamoorthy, 2015), emotional features (Martin and Pu, 2014), and argument features (Liu et al, 2017), from the textural reviews, which are then fed into conventional classifiers such as SVM (Kim et al, 2006) for helpfulness prediction. These methods rely heavily on feature engineering, which is time-consuming and labor intensive.…”
Section: Related Workmentioning
confidence: 99%
“…Motivated by the demand of gleaning insights from such valuable data, review helpfulness prediction has gained increasing interest from both academia and industry communities. Earlier review helpfulness prediction methods rely on a wide range of handcrafted features, such as semantic features (Yang et al, 2015), lexical features (Martin and Pu, 2014), and argument based features (Liu et al, 2017), to train a classifier. The success of these methods generally relies heavily on feature engineering which is labor-intensive and highlights the weakness of conventional machine learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between helpfulness of online reviews and emotions have been explored by Malik and Hussain (2017) where they stud-ied which emotions are important for helpfulness prediction. Martin and Pu (2014) used emotions to detect helpful reviews by applying different classification models (i.e., SVM, Random Forest, and Naïve Bayes) and demonstrated that their approach outperformed methods using POS tagging features. Emotion information has not been considered by any of the existing unsupervised methods.…”
Section: Methodsmentioning
confidence: 99%
“…In majority of the existing work, supervised machine learning models have been employed considering the problem as a predictive task (i.e. predict whether/how useful a review is) (Martin and Pu, 2014;Krishnamoorthy, 2015;Malik and Hussain, 2017;Singh et al, 2017;Wu et al, 2017;Enamul Haque et al, 2018;Alsmadi et al, 2020). With supervised approaches, various types of features such as linguistic features (Krishnamoorthy, 2015;Malik and Hussain, 2017;Wu et al, 2017) or textual features (i.e.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation